How do roots respond to osmotic stress? A transcriptomic approach to address this question in a non-model crop - Zorrilla-Fontanesi, Yasmín; Rouard, M.; Cenci, A.; Kissel, E.; Roux, N.; Swennen, Rony L.; Carpentier, Sebastien C. (2016)
Drought is a complex phenomenon that is relevant for many crops. Performing high-throughput transcriptomics in non-model crops is challenging. The non-model crop where our workflow has been tested on is banana (Musa spp.), which ranks among the top ten staple foods (total production over 145 million tons in 2013 (FAOstat)[1]). Bananas need vast amounts of water and even mild-drought conditions are responsible for considerable yield losses[2]. To characterize drought in the roots of different banana genotypes, we designed a lab model based on osmotic stress (5% PEG treatment for 3 days) and performed mRNA-seq analysis[3]. Using Illumina technology, 18 cDNA libraries were sequenced producing around 568 million high quality reads, of which 70-84% were mapped to the diploid reference genome[4]. We show that the applied stress leads to a drop in energy levels inducing a metabolic shift towards (i) higher oxidative respiration, (ii) alternative respiration and (iii) fermentation. We also analyzed the expression patterns of paralogous genes belonging to the same gene families and detected possible cases of sub-functionalization.